The Influence of Work Stress, Perceived OrganizationalSupport, and Organizational Culture on Work-Life Balance - Nabila Fista Azzahra; Ninik Probosari (TALENTA Publisher, Universitas Sumatera Utara, 2026)
This study aims to determine, examine, and analyze the influence of job stress,perceived organizational support, and organizational culture on work-lifebalance (a study of employees at Banguntapan I and II Community HealthCenters). The population in this study was employees at Banguntapan I and IICommunity Health Centers, with a sample of 79 respondents. Data werecollected through a questionnaire and analyzed using multiple linear regression.The questionnaire was distributed online via Google Forms, then processed andanalyzed using SPSS 25 software.The results indicate that: Job stress has a positive and significant effect onemployee work-life balance; perceived organizational support has a positiveand significant effect on employee work-life balance; and organizational culturehas a negative and significant effect on employee work-life balance.